ISBAT NIKAH TERPADU PERSPEKTIF MAQASID SYARIAH - Hilmy, Ahmad Arif Masdar; Toriqirrama, Faby (Al-Ahwal: Jurnal Hukum Keluarga Islam, 2020)
The purpose of this article is to discuss about the implementation of the trial of integrated marriage validity or isbat nikah terpadu. Based on the Supreme Court Regulation (Perma) No. 1 of 2015, despite Religious Court (PA), the implementation of integrated marriage validity involved the Office of Religious Affairs (KUA). From the perspective of maqāṣid al-sharī'ah, the integrated marriage validity can be considered as an effort of Indonesian government to realize public benefits (maṣlaḥat) as the essence of maqāṣid al-sharī'ah in thefield of marriage affairs. In a broader sense, the existence of the integrated marriage validity could be considered to be able to preserve the religion (ḥifdh al-din), the soul (ḥifdh al-nafs), the intellectual faculty (ḥifdh al-’aql), the offspring (ḥifdh al-nasl), and the property (ḥifdh al-māl).Artikel ini bertujuan untuk membahas tentang pelaksanaan sidang isbat nikah terpadu. Bedasarkan Peraturan Mahkamah Agung RI No. 1 tahun 2015, pelaksanaan isbat nikah terpadu melibatkan dua institusi, yaitu Pengadilan Agama (PA) dan Kantor Urusan Agama (KUA) tempat dilaksanakannya sidang isbat nikah tersebut. Dari persepektif maqāṣid al-sharī’ah, pelaksanaan isbat nikah terpadu dapat dianggap sebagai usaha Pemerintah untuk mewujudkan kemaslahatan umum sebagai inti dari maqāṣid al-sharī’ah dalam bidang perkawinan. Dalam konteks yang lebih luas, pelaksanaan isbat nikah terpadu dapat dikategorikan sebagai usaha nyata Pemerintah dalam menjaga agama (ḥifdh al-din), jiwa (ḥifdh al-nafs), akal (ḥifdh al-’aql), keturunan (ḥifdh al-nasl), dan harta (ḥifdh al-māl).